Illustrated Flora of Bambusoideae in China Volume 2 - Shi, Jun Yi.; Zhang, Yu Xiao.; Zhou, De Qun.; Ma, Li Sha.; Yao, Jun. (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book was compiled by researchers of Chinese Academy of Forestry, Sichuan Agricultural University, Chinese Academy of Sciences, Southwest Forestry University, and Kunming University of Science and Technology. It has been the most comprehensive monograph about the bamboo resources in China until now. "Illustrated Flora of Bambusoideae in China" is composed of two volumes. Volume 2 consists of 18 chapters corresponding to 18 genera of the tribe Arundinarieae (i.e., Acidosasa, Ampelocalamus, Bashania, Chimonocalamus, Drepanostachyum, Fargesia, Ferrocalamus, Gaoligongshania, Gelidocalamus, Indocalamus, Menstruocalamus, Oligostachyum, Pleioblastus, Pseudosasa, Sasa, Sasaella, Thamnocalamus, Yushania). Sixteen forms, 17 varieties, and 397 species in 18 genera are included in this volume (430 taxa in total).
Chimonocalamus -- Drepanostachyum -- Ampelocalamus -- Thamnocalamus -- Fargesia.-Gaoligonshania -- Yushania -- Acidosasa -- Oligostachyum -- Pseudosasa -- Menstruocalamus.-Pleioblastus -- Bashania -- Gelidocalamus -- Sasa -- Sasaella -- Ferrocalamus -- Indocalamus.
Keywords: Plants-Evolution.; Plant ecology; Biodiversity; Plant Evolution; Plant Ecology; Biodiversity